ACTUALITY APPLICATION OF LEGAL PRINCIPLES DURING EMERGENCY SITUATION - Krampuža, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The objective of the research is to analyse the determining principles of the existing and possible limitations and their comprehension during the emergency situation. The tasks of the research are as follows: 1) taking into consideration the limitations and the support measures of the emergency situation identify the principles of the court, which are related to every of these cases, in order to provide the most possible precise compliance of legal solutions to the particular situation; 2) to keep up to date the principles, which are binding to the public administration’s actions during the conditions of the emergency situation.Comparative method has been used for research of the basic principles. The comprehension of the general law in the jurisprudence of the Republic of Latvia’s Constitutional court has been looked for using the historical method, applying these conclusions to the emergency situation. The basic principles for the determining of both the limitations and the support measures have been discussedas well as for the providing of the public administration’s actions by the help of the analytical method. It has been concluded in the research that a good comprehension of the community on its rights and duties, which arises from the nature of the legal principals typical for the emergency situation, will ensure that the community will follow them more willingly and will take them into consideration more effectively. The explanation of the limitations’ influence and meaning to the community takes place through both the implementation demand of the already determined limitations and, particularly separately educating the inhabitants on them. The communication of the legislator with the community has to be developed on the basis of these principles. The effect to be achieved depends on the fact how successful the educating of the community on its rights and duties will be.